Correlates of gastroenterology health-services utilization among patients with gastroesophageal reflux disease: a large database analysis - Wasef Na'amnih; Racheli Katz; Sophy Goren; Amir Ben-Tov; Tomer Ziv-Baran; Gabriel Chodick; Khitam Muhsen (BMC, 2019)
Abstract Background Gastroesophageal reflux disease (GERD) is associated with high utilization of health care services. Diagnostic tests usually are not required to establish GERD diagnosis, but endoscopy is recommended for patients with alarm symptoms such as dysphagia and unintentional weight loss, and those whose symptoms are not relieved by proton pump inhibitors (PPIs) therapy. Evidence on the correlates of utilization of gastroenterology health services among GERD patients is limited. The study aim was to examine associations of patient and physician's characteristics with high utilization of gastroenterology services. Methods In a cross-sectional study using the database of the second largest integrated care organization in Israel, data of all adult GERD patients (N = 75,219) in 2012-2015 were analyzed. High utilization of services was assessed using two dependent variables analyzed separately: undergoing two or more gastroscopies or having six or more visits to a gastroenterology consultant during the study-period. Results Overall, 11,261 (15.0%) patients had two or more gastroscopies and 23,703 (31.5%) had six or more visits to a gastroenterology consultant. The likelihood of high utilization of gastroscopy increased with age; in immigrants from the Former Soviet Union versus patients who were born in Israel; residents of Jerusalem, the south, the north and Haifa districts versus the center district; in patients with high PPI purchases, and in patients who belonged to clinics in which the physician-manger had no board certification. The correlates were similar for visits to a gastroenterology consultant. Conclusions Patient and physician's characteristics were related to high utilization of gastroenterology services among GERD patients. The associations with age and country of birth might reflect more severe disease. The regional differences warrant further research and interventions at the district level. Training in gastroenterology of primary care physicians without a board certification is warranted.